1987
DOI: 10.1002/hed.2890090610
|View full text |Cite
|
Sign up to set email alerts
|

Immunoperoxidase characterization of extramedullary plasmacytoma of the head and neck

Abstract: A retrospective analysis of 18 cases of extramedullary plasmacytoma (EMP) was done to characterize the type of immunoglobulin being synthesized by the neoplastic cells. The immunoperoxidase stain can be performed on previously fixed tissue and offers a means of predicting the likelihood of progression to multiple myeloma (MM). Tumors producing IgG make up the majority of cases of EMP in the literature and only 9% have progressed to MM. Smaller numbers of tumors producing other immunoglobulin classes have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…There may be destruction of adjacent bone in direct continuity with the tumour mass. Poole and Marchetta (1968), Gromer andDuvall (1973), Harwood et al (1981) and Mock et al (1987) felt that the presence of bone destruction seemed to be an unfavourable prognostic factor, while Kotner and Wang (1972), Corwin and Lindberg (1979), Kapadia et al (1982) and Mayr et al (1990) were not of the same opinion. In our series, two of three tumours with bone destruction recurred locally; one of them was a solitary high-grade EMP, and the patient presented with a huge tumour in the paranasal sinuses (Figure 6).…”
Section: Bone Destructionmentioning
confidence: 99%
See 3 more Smart Citations
“…There may be destruction of adjacent bone in direct continuity with the tumour mass. Poole and Marchetta (1968), Gromer andDuvall (1973), Harwood et al (1981) and Mock et al (1987) felt that the presence of bone destruction seemed to be an unfavourable prognostic factor, while Kotner and Wang (1972), Corwin and Lindberg (1979), Kapadia et al (1982) and Mayr et al (1990) were not of the same opinion. In our series, two of three tumours with bone destruction recurred locally; one of them was a solitary high-grade EMP, and the patient presented with a huge tumour in the paranasal sinuses (Figure 6).…”
Section: Bone Destructionmentioning
confidence: 99%
“…The monoclonal gammopathy disappears following treatment of localized primary tumour. Subsequent development of a paraprotein may signal a recurrence (Kapadia et al, 1982;Mock et al, 1987). Holland et al (1992) felt that patients with paraprotein at the time of diagnosis fared worst, while Harwood et al (1981), Soesan et al (1992) and Shih et al (1995) suggested no effect on prognosis provided they return to normal after treatment.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemical characterization of human EMP with immunoglobulin heavy and light chains reveals a monoclonal proliferation of plas-ma cells that secrete a single immunoglobulin type with both λ and K light chains equally represented. 18,19 Previous studies of canine EMP have used a variety of immunohistochemical markers for diagnostic purposes and have determined that canine EMPs are of plasma cell origin. 1,13,20,24 The neoplastic nature of the tumors was confirmed by the identification of a monoclonal expression of immunoglobulin light chains.…”
mentioning
confidence: 99%